DESCRIPTION OF USE OF PERSONAL LISTENING DEVICES (PLD) DURING ONLINE LEARNING DURING COVID-19 PANDEMIC - Agustiawan, Agustiawan (Universitas Pembangunan Nasional Veteran Jakarta, 2021)
Background: Unwise use of personal listening devices (PLD) when learning online during COVID-19 pandemic can increase risk of deafness in future. Methods: This cross sectional study involved 159 respondents (97 students and 62 lecturers) who then filled out a questionnaire regarding their knowledge and attitudes in using PLD. Mann-Whitney test was conducted to see the association between two variable. Results: A total of 51, 55, and 53 respondents respectively used earphones, headsets, and both. A total of 83.0% of respondents knew that they should not use PLD with a volume >60%, 81.1% of respondents knew that they should not use PLD >60 minutes, and as many as 70.4% knew that they should not clean their ears using cotton. bud. Respondents in this study generally never used PLD within >60 minutes (27.7%), rarely used PLD with volume >60% (35.2%), and always cleaned their ears with a cotton bud (48.4%). The bivariate test showed that there was no relationship between the respondent's knowledge of the duration of PLD use >60 minutes (p-value= 0.392) and the volume of PLD usage > 60% (p-value= 0.410), while for the respondent's knowledge in terms of